Combination of Systemic and Topical Treatment for Feline Dermatophytosis: A Case Report - Soedarmanto Indarjulianto; Yanuartono Yanuartono; Alfarisa Nururrozi; Slamet Raharjo; Jeffi Chandra Ajiguna (Acta VETERINARIA Indonesiana, 2020)
Dermatophytoses or ringworm are the most common fungal infections in dogs and cats. This zoonotic disease is called dermatophytosis. A 2 years old male Persian cat referred to the Veterinary Clinic Faculty of Veterinary medicine, Universitas Gadjah Mada with multi-focal circular non-pruritic skin lesions and hair loss mainly on the head and ears. A complete series of dermatologic tests such as Wood’s light examination, direct microscopic examination, and fungal culture were performed. The cat was treated with itraconazole dosage orally for a period of 20 days and ketoconazole topical for 35 days, respectively. Thirty five days after treatments the cat showed reduction of lesions.